Pond Water eDNA Reflects Broad Consistency with Surrounding Terrestrial Plant Ecosystems - Duygu Bozdogan; Shogo Takizawa; Norihiro Furukori; Kosuke Homma; Harue Abe; Hitoshi Sakio; Naoki Harada; Kazuki Suzuki (Biology)
This study evaluates the potential of using pond water eDNA to reflect the surrounding terrestrial plant communities, aiming to develop a sustainable, large-scale, and long-term monitoring method for plant diversity in forest ecosystems. Water samples were collected four times from two ponds with different vegetation types during the late spring to autumn seasons in Japan. eDNA was extracted from dissolved particles fractionated by sequential filtration through pore sizes of 200 µm, 5 µm, and 0.45 µm, followed by high-throughput amplicon sequencing targeting the plant rbcL gene. By comparing field surveys with the eDNA data, we identified 79% and 63% of plant families and genera, respectively, suggesting that pond water eDNA may reflect the surrounding terrestrial plant ecosystem. Additionally, different trends were observed in the seasonal variation of plant taxa and their composition detected in eDNA, based on particle size. This study highlights the potential of pond water eDNA to provide valuable insights into forest plant richness and seasonal dynamics, offering a novel approach for ecological monitoring.